Analysis of gas discharge characteristics across micro-gap under different pressures. (13th August 2021) - Li, Yansen; Sun, Yanzhou; Sun, Yining; Wang, Linhua; Jia, Bin; Chen, Yun
Abstract: To study the process of micro-gap gas discharge under different pressures, the experimental of the micro-discharges for the gaps ranging from 1 to 100 μ m under 1–100 kPa is presented and the results are discussed. The curves of breakdown voltage with the pd value at different gaps are drawn and there are multiple breakdown voltages under the same pd value. As the decrease of the gaps, the deviation between the breakdown curve and the traditional Paschen curve increases when the electrode distance is less than 100 μ m and the pd value is less than about 80 Pa·cm. The breakdown field strength and the ratio of effective secondary coefficient of field emission to Townsend's secondary coefficient are estimated at different pressures and different electrode gaps. The ion-enhanced field effect has been found to play an important role in field emission in several microns of electrode gaps.